2018
DOI: 10.5455/egysebz.20180315041142
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative role of curcumin on the morphological and skeletal malformations induced by betamethasone in rat fetuses

Abstract: ABSTRACT:Among the glucocorticoids, betamethasone has become very popular, being more commonly used for several diseases, to promote organ maturation and to prevent preterm delivery. This work aimed to examining the possible morphological and skeletal malformations induced by betamethasone in foetuses of albino rats an d the role of curcumin as antioxidant against these adverse effects. Administration of betamethasone during the organogenesis phase at a dose equivalent to its human counterpart led to severe in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…In our study, Cur improved the endoskeleton malformation and increased the ossification of whole endoskeleton with improvements in the lengths of long bones of both fore and hind limbs in embryos when compared with SY and Tz groups. Also, a previous study by Badawy et al (2018) showed that oral administration of betamethasone and Cur to pregnant rats caused improvement in fetal growth whether shape, length and body weight. Also, it decreased the skeletal malformation and increases the ossification of whole endoskeleton when compared with the drug group.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our study, Cur improved the endoskeleton malformation and increased the ossification of whole endoskeleton with improvements in the lengths of long bones of both fore and hind limbs in embryos when compared with SY and Tz groups. Also, a previous study by Badawy et al (2018) showed that oral administration of betamethasone and Cur to pregnant rats caused improvement in fetal growth whether shape, length and body weight. Also, it decreased the skeletal malformation and increases the ossification of whole endoskeleton when compared with the drug group.…”
Section: Discussionmentioning
confidence: 93%
“…Ozaki et al (2000) reported that Cur is a potent stimulator of osteoclast apoptosis. Turmeric extracts prevented the activation of the transcription factor NF-κB and suppressed the subsequent expression of genes mediating the destruction of cartilage and bone, including RANK-L, the ligand that binds to and activates the receptor activator for NF-κB (RANK) on osteoclast precursors, which is a necessary and sufficient stimulus for the differentiation of bone-destroying osteoclasts (Wright et al, 2010;Badawy et al, 2018). Turmeric has been used during pregnancy in a variety of traditional medical systems for thousand years and no Western authority recommends against its use during pregnancy (Asher and Spelman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For endo-skeletal preparations, double staining technique was applied as described in a recent study emerged from our laboratory [15].…”
Section: Skeletal Investigationmentioning
confidence: 99%
“…It has been accepted that when embryos or fetuses become maternally subjected to a potentially teratogenic agent, developmental alteration occurs due to their interaction. The final result of this interaction can lead to a number of abnormalities including morphological, skeletal, anatomical, delay in intrauterine growth and development or even fetal death [15,16]. Susceptibility of teratogenicity in an organism towards any teratogen depends on many factors such as critical developmental stage at which the organisms are exposed, the teratogen nature, the dose and route of teratogen and also on the types of initiating mechanism of teratogenesis [17].…”
Section: Body Weight Gain Of Mothersmentioning
confidence: 99%